2017
DOI: 10.5897/ijmms2017.1297
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of patients admitted in intensive care units of Nigist Eleni Mohammed Memorial Hospital of Hosanna, Southern Ethiopia

Abstract: An intensive care unit is a special department of hospital or health care facility that provides intensive treatment medicine. Critically ill patients are admitted to the intensive care unit to reduce morbidity and mortality associated with acute illness, trauma or surgical procedures. This study aimed to assess clinical outcomes of patients admitted in intensive care units of Nigist Eleni Mohammed Memorial Hospital of Hosanna from January 2015 to January 2016. Institutional based cross sectional study design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…Unlike our ndings, Mohammed et al reported that acute abdomen, speci cally small bowel obstruction, was the most common cause of ICU admission (15). The others were septic shock and ARDS (28.2%), acute abdomen and other surgical diseases (18.6%), and severe traumatic brain injury (9%).…”
Section: Discussioncontrasting
confidence: 83%
“…Unlike our ndings, Mohammed et al reported that acute abdomen, speci cally small bowel obstruction, was the most common cause of ICU admission (15). The others were septic shock and ARDS (28.2%), acute abdomen and other surgical diseases (18.6%), and severe traumatic brain injury (9%).…”
Section: Discussioncontrasting
confidence: 83%
“…This difference might be due to factors such as late arrival at the ICU and delay in intervention, shortage of critical emergency drugs, resuscitation ability of the MICU, and absence of airway management equipment in the emergency department [6]. However, this result was different from the study conducted in Ethiopia, where the LOS of ICU mortality was more than 14 days [18].…”
Section: Discussionmentioning
confidence: 75%
“…The determinants of the PICU outcome were based on the seriousness of the condition at admission, patient age, presence of comorbidities, the quality of pre-hospital and emergency trauma care; factors reported during the PICU admission like the use of mechanical ventilation, level of consciousness, duration of the PICU stay; complications during the PICU stay like circulatory and ventilator-related respiratory complications [7][8][9][10]. It is challenging to give effective, and adequate care for the children admitted to the PICU without knowing the causes of admission.…”
Section: Discussionmentioning
confidence: 99%
“…The ICU outcomes were determined by clinical condition at admission, patient age, comorbidity, level of pre-hospital and emergency trauma care, and factors reported during ICU admission, such as the use of mechanical ventilation, level of consciousness, duration of ICU stay, as well as complications during ICU stay, such as circulatory and ventilator-related respiratory complications [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%